Jaundice after multiple halothane anaesthetics administered during the treatment of carcinoma of the uterus. Issue 7 (July 1973) - Davis, P.; Holdsworth, C. D.
Abstract : Halothane is thought to cause hepatitis after multiple exposures in certain susceptible patients. Patients undergoing repeated anaesthetics for insertion of radioactive implants for gynaecological neoplasia appear to be particularly at risk. We are reporting three cases in which hepatitis has followed multiple halothane anaesthetics, and discuss them with reference to our present knowledge of this complication.